Liquid-liquid phase separation in cell physiology and cancer biology: recent advances and therapeutic implications - Huang, Ziyuan; Liu, Zimeng; Chen, Lieqian; Liu, Yanlin; Yan, Gaofei; Ni, Yizheng; Yan, Qiuxia; He, Wenqian; Liu, Junhong; Luo, Shufang; Xie, Jindong (Frontiers in Oncology, 2025)
Liquid-liquid phase separation (LLPS) is a pivotal biophysical phenomenon that plays a critical role in cellular organization and has garnered significant attention in the fields of molecular mechanism and pathophysiology of cancer. This dynamic process involves the spontaneous segregation of biomolecules, primarily proteins and nucleic acids, into condensed, liquid-like droplets under specific conditions. LLPS drives the formation of biomolecular condensates, which are crucial for various cellular functions. Increasing evidences link alterations in LLPS to the onset and progression of various diseases, particularly cancer. This review explores the diverse roles of LLPS in cancer, highlighting its underlying molecular mechanisms and far-reaching implications. We examine how dysregulated LLPS contributes to cancer development by influencing key processes such as genomic instability, metabolism, and immune evasion. Furthermore, we discuss emerging therapeutic strategies aimed at modulating LLPS, underscoring their potential to revolutionize cancer treatment.